Performance of asphalt pavement containing potential cool paving materials - Al-Etba, Salam Ridha Oleiwi (2021)
Asphalt pavement absorbs and stores more heat than natural surfaces. The high surface temperature of the conventional asphalt pavement due to high solar energy absorption, subsequently releases heat into the atmosphere and contributes to the urban heat island (UHI) phenomenon. Previous studies attempt to resolve this issue mainly by using coatings (reflective pavement) and porous asphalt (permeable pavement). However, emphasis was not given on the type of materials used in the asphalt pavement composition. This research aims to produce a cool asphalt mixture based on the modification of asphalt materials that focuses on various waste products. Initially, several samples of asphalt mixtures containing different alternative materials were prepared based on their optical and thermal characteristics. A spectroradiometer was used for indoor measurements of solar reflectance, while an infrared camera and thermocouples were used for outdoor measurements of the surface and internal temperature profiles of the asphalt. The potentially cool paving materials were selected based on the most enhanced thermal properties and highest temperatures decrease compared to conventional sample. In the next phase, the selected materials were then used to modify asphalt and evaluated for microstructural, mechanical, and chemical properties under different ageing conditions (unaged, short-term ageing, and long-term ageing). In the final phase, the slab samples of the selected mixtures were prepared and evaluated in an exposed environmental condition for monitoring their thermal performance, temperature profiles, weather data, and thermophysical parameters, including emissivity and albedo. In addition, the parameters of thermal conductivity and heat capacity were also measured in the laboratory. According to the preliminary test results, the modified asphalt mixtures with waste garnet and coal bottom ash were associated with reduced pavement temperatures compared with conventional pavement at an average of 2°C to 3°C. These materials have also shown their validity as fine aggregates in asphalt pavement by conforming to mechanical, physical and chemical specifications. The thermal performance of asphalt samples containing garnet showed a significant cooling effect followed by bottom ash with better resistance against internal heating and thermophysical properties enhancement. Ageing phenomenon was also discovered to reduce the heat impact as well as the asphalt temperature.